The Economics of Using Solar Energy: School Buildings in Saudi Arabia as a Case Study - Alfaraidy, Faris A.; Sulieman, Hassan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
As a result of increasing population and building of new schools in Saudi Arabia, the demand for electricity is growing rapidly. In this context, the utilization of renewable energy resources such as solar energy appears to goal since it is abundant and holds huge ecological and economic promise. This study aims to provide a new entrance in school buildings’ design and construction by studying the current situation of energy consumption, the possibility of using solar cells, and the economics of its exploitation in school buildings. Interviews were conducted in school buildings at different levels in Arar city as a case study to collect data on energy consumption. Furthermore, a base case school building was selected for studying detailed energy consumption, and then, photovoltaic (PV) energy was proposed to use the on-grid system in accordance with governmental regulations. The study concluded that the use of PV energy in school buildings is economically feasible in addition to that more incentive from the government is needed for wide penetration use in Kingdom Saudi Arabia.